2003
DOI: 10.1038/ng1282
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome stability, in the absence of apoptosis, is critical for suppression of tumorigenesis in Trp53 mutant mice

Abstract: The p53 protein integrates multiple upstream signals and functions as a tumor suppressor by activating distinct downstream genes 1-3 . At the cellular level, p53 induces apoptosis, cell cycle arrest and senescence. A rare mutant form of p53 with the amino acid substitution R175P, found in human tumors, is completely defective in initiating apoptosis but still induces cell cycle arrest 4,5 . To decipher the functional importance of these pathways in spontaneous tumorigenesis, we used homologous recombination to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
279
4
7

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 301 publications
(306 citation statements)
references
References 27 publications
16
279
4
7
Order By: Relevance
“…Apoptosis is an evolutionarily conserved process that enables an organism to remove unwanted or damaged cells (Yu and Zhang, 2005). Several studies have indicated that the induction of apoptosis is an essential function of the tumor suppressor, p53 (Symonds et al, 1994;Schmitt et al, 2002;Liu et al, 2004), and that this function has been shown to exist in both normal (Clarke et al, 1993;Lowe et al, 1993a, b) and cancerous cells (Bunz et al, 1999). Other studies have indicated that this function is conserved in lower eukaryotes, at least in response to DNA damage (Jin et al, 2000;Schumacher et al, 2001;Brodsky et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis is an evolutionarily conserved process that enables an organism to remove unwanted or damaged cells (Yu and Zhang, 2005). Several studies have indicated that the induction of apoptosis is an essential function of the tumor suppressor, p53 (Symonds et al, 1994;Schmitt et al, 2002;Liu et al, 2004), and that this function has been shown to exist in both normal (Clarke et al, 1993;Lowe et al, 1993a, b) and cancerous cells (Bunz et al, 1999). Other studies have indicated that this function is conserved in lower eukaryotes, at least in response to DNA damage (Jin et al, 2000;Schumacher et al, 2001;Brodsky et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several mutations from arginine to leucine at codon 175 (Klein et al, 2001), isoleucine or serine (Ryan and Vousden, 1998) ablate apoptosis activity, but function as wild types in regard to cell cycle arrest, similar to the amino acid adaptation observed in Spalax p53. In a mouse model (Liu et al, 2004) in which p53 R175P mutation was introduced, the initiation of apoptosis was abrogated, whereas cell cycle arrest remained intact. Finally, although apaf1 and mdm2 genes display a high degree of conservation between Spalax and other species, and the effect of Spalax p53 on both human and Spalax target genes is similar, it cannot be ruled out that the altered activity…”
Section: Spalax As a Mammalian Model Organism For Hypoxia Tolerancementioning
confidence: 99%
“…La suppression tumorale a été testée vis-à-vis des deux types de tumorigenèse (spontanée et induite) dans les souris des quatre premières colonnes, et d'un seul (tumorigenèse spontanée ou induite) dans les souris des deux dernières colonnes. *Les souris p53 R172P/R172P sont protégées de la tumorigenèse induite par un dysfonctionnement des télomères, probablement grâce à l'induction de la sénescence, mais pas contre la tumorigenèse doublement induite par un dysfonctionnement télomérique combiné à un traitement par un carcinogène chimique [43,52]. **La suppression de la tumorigenèse spontanée chez les souris p53 25,26/25,26 est controversée [29].…”
Section: P53 Et Effet Warburgunclassified
“…L'inhibition de l'autophagie en constitue possiblement une autre facette : liée également à une expression basale de p53 (dans le cytoplasme), elle prive les cellules d'une souplesse métabolique nécessaire pour leur survie dans des conditions fréquemment rencontrées par les tumeurs naissantes [47]. Le maintien du nombre de centrosomes et de la ploïdie contribue aussi probablement à cette suppression tumorale constitutive [43]. La normalisation des cellules peut éventuellement impliquer un arrêt réversible du cycle cellulaire (flèche brisée) si l'activité de p53 est un peu plus élevée.…”
Section: Autres Cibles De P53 Et Inhibition De L'effet Warburgunclassified